An efficient method for the extraction and the quantitative determination of callose from HLB-affected and healthy citrus - Bernardini, Chiara; Franco, Alessandro; Russo, Riccardo; Livingston, Taylor; Gmitter, Frederick G.; Levy, Amit; Vashisth, Tripti (Frontiers in Agronomy, 2024)
Callose is a 1,3-β glucan responsible for several processes in planta such as cell division, ripening of pollen mother cells, maintaining the plasmodesmata opening, and providing structure to the sieve plates. Besides the physiological roles, callose is deposited during pathogen attacks, forming papillae to prevent pathogen entrance into the tissue or plugging the sieve pores to limit the spread of phloem pathogens. Candidatus Liberibacter asiaticus (CLas), the putative causal agent of Huanglongbing (HLB), is a phloem-restricted pathogen whose infection leads to the production of callose in the phloem. Characterizing the dynamics of callose plugging during HLB is important for understanding the disease, but no published protocols are available for the extraction and quantification of the callose in citrus trees, and quantitative data are limited. Detection of callose by microscopy is time-consuming and expensive and does not give information about the distribution of callose in the entire plant. Here, we present a short protocol for the efficient extraction and quantification of the total callose from citrus plants. We compared different tissues from healthy and CLas-infected plants and identified an increase in callose levels in the midribs, the stems, and the fruit peduncles of infected plants. Callose levels were highest in leaves, especially midribs, compared to stems, roots, and fruit peduncles. This method could be applied to other woody plant species.